Aprendizagem e internacionalização em pequenas e médias empresas: um estudo sobre empresas moveleiras do Rio Grande do Sul (Brasil) - Schilling, Luís Felipe (Universidade do Vale do Rio do Sinos, 2007)
The objective of this work is to analyze aspects that support and impose difficulties to the processes of learning that occur during the internationalization on a group of furniture companies from Mountains Region of Rio Grande do Sul state (Brazil). The participant of the study companies’ cases and its internationalization are described. The processes of organizational and interorganizational learning tied to the internationalization are described based on “4Is” model and in the relations between processes of learning and stages of internationalization. The case study is of exploratory and descriptive nature and the research strategy is a study of an incorporated single case, with 4 analysis units. The description of the internationalization processes suggests that the companies adopt the perspective of the experiential learning as an internationalization strategy. For the intuition process – opportunity prospection, the exportation appears as an option to be considered. For the interpretation and integratio
Keywords: indústria moveleira; internacionalização; Rio Grande do Sul; aprendizagem organizacional; furniture industry; internationalization; organizational learning; Ciências Sociais Aplicadas